2016
DOI: 10.1186/s12936-016-1164-2
|View full text |Cite
|
Sign up to set email alerts
|

Small-scale land-use variability affects Anopheles spp. distribution and concomitant Plasmodium infection in humans and mosquito vectors in southeastern Madagascar

Abstract: BackgroundDeforestation and land-use change have the potential to alter human exposure to malaria. A large percentage of Madagascar’s original forest cover has been lost to slash-and-burn agriculture, and malaria is one of the top causes of mortality on the island. In this study, the influence of land-use on the distribution of Plasmodium vectors and concomitant Plasmodium infection in humans and mosquito vectors was examined in the southeastern rainforests of Madagascar.MethodsFrom June to August 2013, health… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 23 publications
0
22
0
Order By: Relevance
“…Here, our first step was to establish the baseline species composition, by collecting live mosquitoes in traps or bags and identifying them using microscopy. We found both Anopheles and Culex mosquitoes ( Zohdy et al, 2016 ), which we identified only to genus level in the field. We recorded several minutes of acoustic data from both, to form a frequency distribution reference database specific to the RNM field site, for comparing new data from phone recordings ( Figure 4A,B ).…”
Section: Resultsmentioning
confidence: 75%
“…Here, our first step was to establish the baseline species composition, by collecting live mosquitoes in traps or bags and identifying them using microscopy. We found both Anopheles and Culex mosquitoes ( Zohdy et al, 2016 ), which we identified only to genus level in the field. We recorded several minutes of acoustic data from both, to form a frequency distribution reference database specific to the RNM field site, for comparing new data from phone recordings ( Figure 4A,B ).…”
Section: Resultsmentioning
confidence: 75%
“…Marrama et al (1995) showed rice elds had the highest percentage of mosquito larvae and provide half of all positive larval breeding habitats (59). Zohdy et al (2016) demonstrated that Anopheles species are the dominant mosquitoes in agricultural and village settings, and are the minority in forest settings (28).…”
Section: Discussionmentioning
confidence: 99%
“…In eastern humid tropical forest, Anopheles mosquitoes are more abundant in agricultural land and village environments than surrounding forests, indicating forest clearance as a possible driver of local malaria transmission (28). A cross-sectional study of communities in southeast Madagascar demonstrated that bed net use protected against malaria, while rural individuals in lower socioeconomic brackets, between 6-14 years of age, were at higher risk of infection (23,29).…”
mentioning
confidence: 99%
“…The influence of logging per se on adult mosquito communities has not yet been directly examined, but several prior studies have examined how urbanisation or land‐use gradients, which integrate a suite of landscape changes including loss of intact forest, influence adult mosquito communities. Studies of land‐use gradients in the Peruvian Amazon (Johnson et al ., ), Thailand (Thongsripong et al ., ), Spain (Ferraguti et al ., ), Madagascar (Zhody et al ., ), and remote Australian islands (Meyer Steiger et al ., ) generally find the highest mosquito abundance and diversity in rural, forested sites with high vegetative cover relative to more urban habitats. However, in Anopheles species, the combined effects of deforestation and conversion to agriculture are highly species‐specific, with some taxa increasing in abundance with land‐use change, and others decreasing (Yasuoka & Levins, ).…”
Section: Introductionmentioning
confidence: 99%
“…Although the impacts of deforestation on vector ecology and resulting disease risk have been of long-standing interest (reviewed in Walsh et al, 1993), only recently have studies explicitly considered how anthropogenic changes to intact forests alter the diversity and abundance of the invertebrate taxa that commonly serve as disease vectors (e.g. Thongsripong et al, 2013;Meyer Steiger et al, 2016;Zhody et al, 2016).…”
Section: Introductionmentioning
confidence: 99%